PTU-040 Daily consultant delivered ward care: effects on inpatient stay and patient care. (17th June 2017) - Rej, A; Johal, S; Thoufeeq, M
Abstract : Introduction: The role of the ward round is crucial in managing inpatient care, and its importance is often neglected, as highlighted by the Royal College of Physicians (RCP) 1 . A daily consultant led approach was reviewed at the Northern General Hospital, Sheffield Teaching Hospitals NHS Foundation Trust. Method: From November 2015, a new method of working was implemented, with a consultant of the day to review new admissions to gastroenterology, twice during the day, at 8am and 3pm, as well as performing any new emergency inpatient endoscopy. In addition to this, ward based consultants were allocated (2 luminal and 2 hepatology) to cover ward rounds daily on the new system. This was done on a rotational basis. Prior to this, consultants would review patients on the ward approximately twice a week, with a consultant reviewing new patients at 8am only, without an allocated consultant for the day. Data was retrospectively compared from April-Oct 2015, prior to implementation, to November 2015-November 2016, after implementation. Results: Implementation of consultant of the day and ward based consultants led to a reduction in daily bed occupancy (median 83 vs 77 beds), reduced length of non-elective stay (median 7.40 vs 6.79 days), reduction in number of outliers (median 24 vs 19 inpatients), reduced monthly re-admission rate (median 3.19% vs 3.08%), greater proportion of early discharges (median 65% vs 60% stay <1 week) and reduction in Datix complaints (median 11.0 vs 10.5 complaints). Conclusion: The data suggests that daily consultant ward rounds and reviews may result in reduced inpatient stay, early discharges, appropriate bed allocation and reduced complaints. Reference: . Royal College of Physicians and Royal College of Nursing. Ward rounds in medicine: principles for best practice. London: RCP, 2012. Disclosure of Interest: None Declared